Microvesicles derived from human Wharton's jelly mesenchymal stem cells promote human renal cancer cell growth and aggressiveness through induction of hepatocyte growth factor. - Tao Du; Guanqun Ju; Shuai Wu; Zhongliang Cheng; Jun Cheng; Xiangyu Zou; Guangyuan Zhang; Shuai Miao; Guohua Liu; Yingjian Zhu (PLoS ONE)
In our previous study, microvesicles (MVs) released from human Wharton's jelly mesenchymal stem cells (hWJ-MSCs) retard the growth of bladder cancer cells. We would like to know if MVs have a similar effect on human renal cell carcinoma (RCC). By use of cell culture and the BALB/c nu/nu mice xeno-graft model, the influence of MVs upon the growth and aggressiveness of RCC (786-0) was assessed. Cell counting kit-8 (CCK-8) assay, incidence of tumor, tumor size, Ki-67 or TUNEL staining was used to evaluate tumor cell growth in vitro or in vivo. Flow cytometry assay (in vitro) or examination of cyclin D1 expression (in vivo) was carried out to determine the alteration of cell cycle. The aggressiveness was analyzed by Wound Healing Assay (in vitro) or MMP-2 and MMP-9 expression (in vivo). AKT/p-AKT, ERK1/2/p-ERK1/2 or HGF/c-MET expression was detected by real-time PCR or western blot. Our data demonstrated that MVs promote the growth and aggressiveness of RCC both in vitro and in vivo. In addition, MVs facilitated the progression of cell cycle from G0/1 to S. HGF expression in RCC was greatly induced by MVs, associated with activation of AKT and ERK1/2 signaling pathways. RNase pre-treatment abrogated all effects of MVs. In summary, induction of HGF synthesis via RNA transferred by MVs activating AKT and ERK1/2 signaling is one of crucial contributors to the pro-tumor effect.